Geochemistry of soils formed on ophiolite rocks in the Al-Bassit region of Northwestern Syria - سمر غانم; أحلام إبراهيم (Latakia University Journal -Biological Sciences Series, 2024)
The al-Bassit region is characterized by ophiolite rocks with distinct chemical compositions and characteristics. Six soil profiles formed on ophiolite rocks (basic and ultra-basic) were selected to determine the chemical composition and intensity of weathering processes in these soils. Nineteen samples of profiled soil were selected, and some of their morphological, physical, and chemical properties were studied. Weathering indexes were also calculated (CIA, WIP, CIW…), The results showed that the behavior of chemical elements is influenced by parent materials, and that all profiles are generally located within the weak weathering range, especially profiles P4 and P1, which are derived from basalt and serpentine rocks, respectively. Except for profile P3, which is derived from fine-grained gabbro rocks, it has been exposed to moderate-intensity weathering.